2021
DOI: 10.3889/oamjms.2021.6368
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Activity of Myoepithelial Cells in of Mucoepidermoid Carcinoma

Abstract: AIM: The aim of the study is to investigate the role of myoepithelial cells in the pathogenesis of mucoepidermoid carcinoma (MEC) using the double immunohistochemical staining; α _smooth muscle actin (_α-SMA)as specific marker for the myoepithelial cell differentiation and proliferative cell nuclear antigen (PCNA) as a marker for proliferative activity of myoepithelial cells. MATERIAL AND METHODS: Retrospective study of twenty salivary gland specimens (ten MEC and ten normal salivary glands) were studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…Both immunohistochemistry and histopathological examinations of SACC specimens show biphasic elements in the development of the tumor, which are myoepithelial cells and glandular/secreting epithelial cells, with the former being predominant in most of the SACC cases. A study based on immunohistochemistry labelling indicated that myoepithelial cell proliferation and differentiation in SACC contributed to the disease's carcinogenesis progress more than its epithelial/secreting counterpart [ 76 ]. Furthermore, because submandibular ACC often demonstrates more proliferation of the myoepithelial cells and less differentiation than that of the parotid gland, the study concluded that this could potentially explain the aggressive clinical behavior of the submandibular ACC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both immunohistochemistry and histopathological examinations of SACC specimens show biphasic elements in the development of the tumor, which are myoepithelial cells and glandular/secreting epithelial cells, with the former being predominant in most of the SACC cases. A study based on immunohistochemistry labelling indicated that myoepithelial cell proliferation and differentiation in SACC contributed to the disease's carcinogenesis progress more than its epithelial/secreting counterpart [ 76 ]. Furthermore, because submandibular ACC often demonstrates more proliferation of the myoepithelial cells and less differentiation than that of the parotid gland, the study concluded that this could potentially explain the aggressive clinical behavior of the submandibular ACC.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recurrent and metastasized adenoid cystic carcinoma (R/M ACC) can resist the treatment for more extended periods and make disease management challenging. Some studies reported a better prognosis in females and younger patients with 5-, 10-, and 15-year survival rates of 90.34%, 79.88%, and 69.22%, respectively [ 76 ]. A recent study published in 2020 reported a lower overall survival rate for 5 and 10 that vary between 68% to 80% and 52% to 65%, respectively, but the study sample was small ( N = 49] [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The resistance of recurrent and metastasized ACC to treatment over lengthy durations further complicates disease control. Research has shown a more favorable prognosis in younger patients and females, with survival rates of 90.34%, 79.88%, and 69.22% at 5, 10, and 15 years, respectively [ 87 ]. However, a 2020 study with a small sample size of 49 participants reported overall survival rates varying between 68% to 80% for 5 years and 52% to 65% for 10 years, with long-term survival rates ranging from 23% to 40% [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have revealed the multiple roles of the MECs, such as glandular development, homeostasis, maintenance of the glandular normal structure, secretion of BM material, contractility, metabolic and electrolyte exchanges between the luminal epithelial cells and stroma, the transmission of neural stimuli, and promotion of tumor suppression [ 27 , 29 , 30 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…MECs have key roles in glandular morphogenesis, promoting glandular epithelial cell development and differentiation, due to their GFs, like CD109 and FGF2 [ 27 , 29 , 59 ].…”
Section: Introductionmentioning
confidence: 99%